Implementation of 21st century learning and the challenges - Mohd Rusdin, Norazlin; Ali, Siti Rahaimah (2018)
The purpose of this study is to identify the implementation of 21st century learning among teachers. Teachers play important role in determining the outcomes of 21st century learning. There are many factors influence teaching practice in 21st century classroom. Knowledge, resources, facilities and professional development have contributed big effect on the teaching quality. A qualitative research involved 20 teachers has been carried out to know teachers’ opinion regarding to the implementation of 21st century learning in their teaching practice. A semi structured interview session was conducted with all the participants to collect information related to four main points which comprise: i) teachers’ opinion; ii) teaching practice; iii) the constraints and challenges and iv) suggestions for improvement related to the implementation of 21st century learning. The responds from all participants were transcribed and analysis according to the themes. The findings show that teachers have positive views regarding to 21st century learning but they still need to make improvement in teaching practice. Teachers faced many challenges related to time constraint, insufficient knowledge and inadequate resources and ICT facilities. Teachers have contributed some suggestions to improve all the challenges which including: i) professional development; ii) provide resource; iii) provide teaching module and iv) upgrade the quantity and quality of ICT facilities and tools.